The paradox of phase transitions - Mierau, Johannes (Technische Universität Dortmund, 2021)
In this thesis I present a novel solution to the paradox of phase transition, a problem that has gained extensive attention from philosophers of physics over the last twenty years. The paradox consists in the contrast between a theoretical consequence of statistical mechanics which asserts that phase transitions require infinite amounts of substance and disproving observations of phase transitions in finite systems. The fact that it is widely neglected by physicists considerably challenges the philosophical idea of the rationality of that science. Besides these philosophical worries about the apparent contradiction, the study of phase transitions illuminates a wide range of hotly debated topics from the philosophy of science, like asymptotic reasoning as a new kind of scientific explanation, the problem of indispensable counterfactual idealisations, as well as limitations of reductionism and potential emergent phenomena in physics. Unlike many other philosophers, I do not choose a revisionist approach that rectifies the theoretical approach to phase transitions in physics from a philosophical perspective, I rather argue that the paradox is the result of the underlying conception of scientific representation. In order to dissolve the paradox, I propose an alternative account of how theoretical models represent empirical objects that reflects the inherent imprecise nature of theories of empirical sciences. It successfully resolves the tension between the theoretically required infinite models and the finiteness of empirical objects, as it admits that the former represent the latter. Altogether, my thesis is evidence of the utility of the methods of general philosophy of science for the philosophy of the particular sciences. It is the first concrete application of the structuralism of theories that emphasises the importance of accounting for the imprecise nature of physical theories and shows how its central formal tool of admissible blurs successfully solves a pending problem from the philosophy of physics.
a structural of phase transitions
Keywords: reduction; paradox of phase transitions; structuralism of physical theories; 200; 230; 100; 300; 150; 320; Reduktion <Phänomenologie>; Wissenschaftstheorie